(untitled) (Journal of Cancer Research Updates, 2015)
Purpose: Diagnosis and perioperative management of bilateral adrenal pheochromocytoma with a successful outcome is an apt combination of clinical knowledge and anaesthetic skills. Detailed history, meticulous physical examination, relevant laboratory investigations along with good preoperative pharmacological optimization and fluid resuscitation plays an important role in the perioperative period. Genetic testing and counseling should be offered to all the family members of patients suspected of familial predisposition. We report the anesthetic management of 10 year old male child with bilateral adrenal pheochromocytoma with family history of disease. Clinical Features: A10-year old male, presented to our pediatric outpatient clinic with gradually increasing holocranial headache, blurring of vision, sweating, photophobia, progressive quietness in nature and poor performance in school, increased thirst and urine output for one week along with pain over bilateral lower limbs and difficulty walking without support for 20days. Parents also reported two episodes of generalized convulsions with one episode of opisthotonic posturing and up rolling of eyes, which was sustained for 50 min. Family history of three sudden deaths, and father, a known case of pheochromocytoma along with clinical presentation, raised the suspicion of familial pheochromocytoma. Conclusion: Though pheochromocytomas are rare tumours, a high level of suspicion in paediatric age group, where patients don’t present with classical symptoms, leads to early diagnosis and management and prevents catastrophic events. Young patients with bilateral disease and positive family history should be offered genetic testing. Preoperative catecholamine blockade and meticulous anaesthetic and surgical management are the keys to successful perioperative management of bilateral pheochromocytoma.